Moral Heroes Look Up and to the Right. (March 2016) - Frimer, Jeremy A.; Sinclair, Lisa
Portraits of moral heroes often portray the hero gazing up and to the viewer's right in part because ideologically minded followers select and propagate these images of their leaders. Study 1 found that the gaze direction of portraits of moral heroes (e.g., Martin Luther King, Jr.) tend to show the hero looking up-and-right more often than chance would predict, and more often than portraits of celebrities (e.g., Elvis Presley) do. In Studies 2 and 3, we asked participants to play the role of an ideologically motivated follower, and select an image of their leader to promote the cause. Participants preferentially selected the up-and-right version. In Study 4, we found that conceptual metaphors linking directionality to personal virtues of warmth, pride, and future-mindedness helped explain why the up-and-right posture looks most heroic. Followers play an active role in advancing social causes by portraying their leaders as moral heroes.